Myth and Organizational Culture: A Comparative Study of Religious and Secular Workplaces - Shraah, Ata Elayyan Mohammad Al (iRASD Journal of Management, 2023)
Saudi Arabian Religious and secular companies are compared to examine the intricate interaction between organisational myths and workplace culture. We want to identify the most prominent misconceptions in each workplace type, assess how they affect employee commitment and organisational conduct, and examine how rituals and leadership style mediate them. Based on Schein, Ashforth & Humphrey and Gioia et al.'s organisational culture and leadership theories, the study collects quantitative and qualitative data using mixed methodologies. Religious and secular staff are questioned with Likert scales and open-ended questions. Research by Ashforth & Humphrey and Gioia et al. supports the questionnaire's reliability and validity. Theme analysis of open-ended responses and interviews reveals organisational myths and effects. Saudi respondents came from varied sectors, making conclusions generalizable. Research shows religious and secular firms have separate mythology, rituals, and leadership. Secular groups encourage equality and creativity, while religious ones emphasize creation stories and allegiance. Religious and secular organizations’ daily prayers and team-building effect organisational conduct. Religious leaders' justice and communication boost staff loyalty. This research advances theory and practice. Myth frameworks, organisational culture, and leadership theories are used to analyse how myths shape workplace dynamics. Workplace customs and leadership style strengthen theory. Findings can assist leaders align company narratives, strengthen culture through rituals, and establish values-based leadership. Organisational life's multifaceted relationships are revealed in this study to promote leadership growth, change, and cultural management.